Research on Temperature Field Distribution of Limited Slip Clutches Based on Dynamic Heat Flow Distribution - Chen Qiao'er; Li Xueliang; Peng Zengxiong; Jin Jiaxi; Yang Shujun; Lian Zhuang (Jixie chuandong)
In order to accurately study the temperature field distribution during the long-term sliding friction process of the limited slip clutch, Fluent software is used to solve the flow field velocity distribution of the friction pair under different working conditions to obtain the average convective heat transfer coefficient and calculate the cooling power of the lubricating oil. A dynamic heat flow distribution temperature prediction model is established with the constraint of continuous friction contact surface temperature by the heat balance method, and a long-time sliding friction test is designed to verify the analysis results. The results show that under the condition of the constant heat flow input, there is a temperature difference between the steel disc and the friction plate, which increases with time, the temperature prediction results are higher than the experimental values, and the maximum deviation is 22.2 K. The predicted deviation of the dynamic heat flow distribution temperature model is within 8.1 K. The input heat power at each position on the surface of the steel disc sheet decreases with time and tends to a fixed value. The equilibrium temperature is distributed in a parabola along the radial direction and reaches a peak at the place between the mid and the outer diameter.